2021
DOI: 10.1055/s-0041-1730938
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Spectrum of Severe Hypernatremia in Infants with Neurological Manifestations

Abstract: Background Variable neurological manifestations and imaging findings have been described in children with severe hypernatremia. We aimed to describe the spectrum of neuroimaging changes in infants with severe hypernatremia. Methods This retrospective study included infants with severe hypernatremia (serum sodium >160 mEq/L), abnormal neurological examination, and an abnormal magnetic resonance imaging (MRI) of the brain over a period of 2 years in a tertiary care hospital. Relevant clinical data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…We found that hypernatremia was associated with the MRI degree of brain injuries and almost all (93.3%) patients with hypernatremia had subdural hemorrhage. The primary consequence of hypernatremia is the shrinkage of cerebral cells that resulting in the brain being pulled away from the overlying calvarium, leading to the tearing of bridging veins and the occurrence of extensive subdural hemorrhage (30,31). Our data further showed that hypernatremia was associated with increase occurrence of white matter injury.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We found that hypernatremia was associated with the MRI degree of brain injuries and almost all (93.3%) patients with hypernatremia had subdural hemorrhage. The primary consequence of hypernatremia is the shrinkage of cerebral cells that resulting in the brain being pulled away from the overlying calvarium, leading to the tearing of bridging veins and the occurrence of extensive subdural hemorrhage (30,31). Our data further showed that hypernatremia was associated with increase occurrence of white matter injury.…”
Section: Discussionsupporting
confidence: 60%
“…Our data further showed that hypernatremia was associated with increase occurrence of white matter injury. In a previous study on severe hypernatremia (serum sodium >160 mmol/L) in infants showed the incidence of white matter injuries was up to 70% (31). Experimental data in rats have demonstrated that acute hypernatremia can result in enduring histological brain damage, which includes myelinolysis of the white matter and neuronal necrosis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Infants with sodium levels of 150 mEq/L and above should be offered a brain MRI during admission, given that 45.2% are positive for lesions consistent with injury at this level [ 11 , 77 ]. They should also be offered developmental follow-up evaluation given the known increased risk of developmental problems associated with sodium levels ≥ 150 mEq/L [ 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%